Um Sistema Baseado em Instituições Eletrônicas para Apoio ao Intercâmbio de Documentos Históricos Autenticados Através de Bibliotecas Digitais - Silva, Rosaura Espírito Santo da (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2010)
In this paper, Electronic Institutions are used as a model to develop a system designed to support the exchange of authenticated digitalized historical documents through digital libraries. The architecture is modeled using UML diagrams as well as diagrams specific to Electronic Institutions. The work aims to contribute to the use of digital libraries as a means for the exchange of authenticated digitalized historical documents.